2018
DOI: 10.1017/jfm.2018.205
|View full text |Cite
|
Sign up to set email alerts
|

Mean shear versus orientation isotropy: effects on inertialess spheroids’ rotation mode in wall turbulence

Abstract: The orientation of spheroidal particles dispersed in a fluid flow is known to influence the particles’ rotation mode. Rod-like and disk-like particles orient themselves differently and accordingly also rotate differently. In order to explore the role of the deterministic factors, i.e. mean shear and vorticity anisotropy, on the orientational behaviour of inertialess tracer spheroids, we adopted a purpose-made Couette–Poiseuille flow simulated numerically by Yang et al. (Intl J. Heat Fluid Flow, vol. 63, 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…disks spin but rods tumble. The existence of two such qualitatively different modes of particle rotation, namely the 'centre mode' and the 'wall mode', has been documented in our recent studies (Zhao et al 2015;Yang, Zhao & Andersson 2018). However, the fluid dynamical features of a turbulent channel flow vary considerably from the buffer region where the 'wall mode' prevails, to the channel centre, which resembles HIT, and where the 'centre mode' rotation is found.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…disks spin but rods tumble. The existence of two such qualitatively different modes of particle rotation, namely the 'centre mode' and the 'wall mode', has been documented in our recent studies (Zhao et al 2015;Yang, Zhao & Andersson 2018). However, the fluid dynamical features of a turbulent channel flow vary considerably from the buffer region where the 'wall mode' prevails, to the channel centre, which resembles HIT, and where the 'centre mode' rotation is found.…”
Section: Introductionmentioning
confidence: 75%
“…(2015 b ), Zhao & Andersson (2016) and Yang et al. (2018). Herein, however, we focus on both inertial and tracer particles.…”
Section: Mathematical Modelling and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…These tendencies were recently associated with deformations of Lagrangian fluid elements. The preferential alignment of rods and disks with Lagrangian stretching and compression directions, respectively, was first reported in HIT [7] and subsequently in wall turbulence [8,9]. Computational [10,11] and experimental [12,13] studies have confirmed the role of the preferential alignment on the rotational particle behavior, such as spinning of rods and tumbling of disks.…”
Section: Introductionmentioning
confidence: 80%
“…The intricate behavior of non-spherical particles in three-dimensional flow fields has been studied in HIT [5,7,10] as well as in wall turbulence [6,9,14]. These studies have all been carried out in statistically steady flow fields.…”
Section: Introductionmentioning
confidence: 99%